2007
DOI: 10.1121/1.2759165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of porosity on effective diagonal stiffness coefficients (cii) and elastic anisotropy of cortical bone at 1MHz: A finite-difference time domain study

Abstract: Finite-difference time domain (FDTD) numerical simulations coupled to real experimental data were used to investigate the propagation of 1 MHz pure bulk wave propagation through models of cortical bone microstructures. Bone microstructures were reconstructed from three-dimensional high resolution synchrotron radiation microcomputed tomography (SR-muCT) data sets. Because the bone matrix elastic properties were incompletely documented, several assumptions were made. Four built-in bone matrix models characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…Accordingly, the local mesoscale porosity in samples taken from cortical bone cross sections is that which is effectively assessed with standard techniques. It is defined as that due to the Haversian canals and resorption cavities and lies in the range of 5-15 per cent (Bousson et al 2001;Dong & Guo 2004;Baron et al 2007). However, note that the macroscopic porosity defined as an average of the mesoscopic porosity over local representative volume element (RVE) locations varies much less and is usually in the range of 7-9 per cent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the local mesoscale porosity in samples taken from cortical bone cross sections is that which is effectively assessed with standard techniques. It is defined as that due to the Haversian canals and resorption cavities and lies in the range of 5-15 per cent (Bousson et al 2001;Dong & Guo 2004;Baron et al 2007). However, note that the macroscopic porosity defined as an average of the mesoscopic porosity over local representative volume element (RVE) locations varies much less and is usually in the range of 7-9 per cent.…”
Section: Introductionmentioning
confidence: 99%
“…All these models consider elementary shapes for the pores and simple mesostructure. Recently, Baron et al (2007) and Grimal et al (2008) have developed numerical models to compute the effective properties of cortical bone with realistic mesoscale structures derived from images. However, these latter models are not appropriate to use when performing systematic parametric studies due to their high computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of porosity on material properties is directional anisotropy [108,109]. Young's and shear modulus in human femoral cortical bone samples correlate with porosity in the longitudinal, but not the transverse, direction [109].…”
Section: Condition E Longitudinal (Gpa) E Transverse (Gpa)mentioning
confidence: 99%
“…Young's and shear modulus in human femoral cortical bone samples correlate with porosity in the longitudinal, but not the transverse, direction [109]. In addition, increasing porosity correlates with decreased anisotropy [108,109]. In general, pore spaces in bone preferentially align with the long axis of the bone.…”
Section: Condition E Longitudinal (Gpa) E Transverse (Gpa)mentioning
confidence: 99%
“…It is has been shown that the porosity in the radial direction (which is defined in the bone's cross-section plan) is heterogeneous [13,14]. As the macroscopic mechanical properties of bones strongly depend on its porosity [15,16], cortical bone would naturally be considered as a functionally graded material. Thus the model employed in this study involves an anisotropic elastic plate sandwiched between two homogeneous fluids and having varied elastic properties in the through-thickness direction.…”
Section: Introductionmentioning
confidence: 99%